Myocardial Perfusion SPECT and ATTR imaging 2021 in Germany: Results of the 9th Survey - Lindner, Oliver; Schaefer, Wolfgang Michael; Silber, Sigmund; Rischpler, Christoph; Burchert, Wolfgang (Nuklearmedizin - NuclearMedicine, 2023)
Aim This paper presents the results of the 9th survey of myocardial perfusion SPECT (MPS) from the reporting year 2021.Methods 218 questionnaires (131 practices (PR), 58 hospitals (HO), 29 university hospitals (UH)) were evaluated. Results of the last survey 2018 are set in squared brackets.Results MPS data from a total of 133,057 [145,930] patients (–8.8%) with 131,868 [143,707] stress and 106,546 [121,899] rest MPS were analysed. A comparison with official data revealed that 54% all MPS were recorded. From 2018 to 2021, official data showed a every year an increase in MPS numbers. On average, 610 [502] MPS patients (+22%) were examined in each department. 74% [69%] of the responders reported an increase or no changes in their MPS patient numbers. Ambulatory care cardiologists represented as always, the mayor referral group (68% [69%]). For the first time, pharmacological stress was more frequently applied than ergometry (42% [51]). Regadenoson was mostly used. The use of the different protocols remained nearly unchanged. Two-day protocols were predominantly applied (49% [48%]). A shift from multi-headed cameras (58% [72%]) to SPECT-CT systems (24% [17%]) was found. Attenuation correction was performed in 33% [26%] of all MPS. 88% [86%] of all stress, 88% [87%] of all rest and 87% [83%] of all stress and rest MPS were acquired as gated SPECT. 72% [67%] of all departments performed scoring by default. The number of departments without scoring decreased to 13% [16%].Conclusions The MPS Study 2021 shows that the long-term positive development of MPS imaging in Germany is continuing. The COVID-19 pandemia did not change this trend. The procedural and technical details of MPS imaging reveal a high level of guideline conformity.
Keywords: Myocardial perfusion SPECT, ATTR imaging, utilization review, utilization statistics, numerical data